Planning for FEWsheds: The Role of Planning in Integrating and Strengthening Food, Energy and Water Systems. (February 2023) - Brinkley, Catherine; Raj, Subhashni; Raja, Samina
As climate change and increased frequency of extreme weather events threaten local and national Food, Energy and Waters (FEW) systems, policymakers and planners are asked to secure the long-term sustainability of resources and address disaster management where failure in one system has cascading effects. The explicit acknowledgment of interdependencies and equity across FEW systems and scales of governance is an approach we term planning for "FEWsheds." With this research, we build an integrated framework for understanding FEW supply, equity outcomes, available data, and efforts to make FEW systems more resilient through diversification, distributed systems, or relocalization. The literature review demonstrates common flaws in both research design and policy approaches. For example, few studies explicitly address demographic characteristics. Higher-income households use more water, energy and land; are less responsive to price signaling; and often do not bear the negative externalities of infrastructure siting compared to low-income families, who are, in turn, the most vulnerable to supply disruption and contamination. A FEWshed framework helps make apparent the regional interdependencies, inefficiencies and disparities so that policymakers can take corrective action in fostering just, vibrant and sustainable communities for all constituents.